Analisis faktor yang berhubungan dengan kepatuhan konsumsi tablet Fe pada remaja putri - Aryanti, Riski; Hermawan, Dessy; Yanti, Dhiny Easter (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Cases of anaemia in East Lampung Regency show a tendency for a high number of cases; in 2020, after screening for haemoglobin (HB), it was recorded that the percentage of anaemia was 5.14%.Purpose: Analyzing factors related to compliance with Fe tablet consumption among young women at Way Jepara 1 Senior High School, East Lampung.Method: This research is observational analytic research with a cross-sectional design. The sample consists of adolescents of classes I and II at Way Jepara 1 Senior High School, East Lampung Regency, with as many as 150 respondents. Data analysis uses univariate, bivariate, and multivariate methods.Results: The hypothesis shows that there is an influence of knowledge (p=0.000; OR=3.6), attitude (p=0.000; OR=5.2), motivation (p=0.007; OR=2.7), peer support (p = 0.003; OR=2.9), support from health workers (p=0.000; OR=3.7), and teacher support (p=0.014; OR=2.4) on compliance with Fe tablet consumption in adolescent girls. Multivariate analysis showed that the most dominant variable in adherence to consuming Fe tablets in young women was knowledge (p=0.000; OR=9.5).Conclusion: There are factors that are significantly related to compliance with Fe tablet consumption, such as knowledge, attitude, motivation, peer support, health worker support, and teacher support.Suggestion: In order to improve scheduled health promotion regarding the benefits of Fe tablets and carry out HB checks at least once a year.Keywords: Anaemia; Compliance with Fe Tablet Consumption; Young Girl.Pendahuluan: Kasus anemia di Kabupaten Lampung Timur menunjukkan kecenderungan jumlah kasus yang tinggi; Pada tahun 2020, setelah dilakukan skrining hemoglobin (HB), tercatat persentase anemia sebesar 5.14%.Tujuan: Menganalisis faktor-faktor yang berhubungan dengan kepatuhan konsumsi tablet Fe pada remaja putri di SMA Negeri I Way Jepara Lampung Timur.Metode: Penelitian ini merupakan penelitian observasional analitik dengan rancangan cross sectional. Sampelnya adalah remaja kelas I dan kelas II di SMAN 1 Way Jepara Kabupaten Lampung Timur sebanyak 150 responden. Analisis data menggunakan univariat, bivariat dan multivariat.Hasil: Hasil hipotesis menunjukkan bahwa ada pengaruh pengetahuan (p=0.000; OR=3.6), sikap (p=0.000; OR=5.2), motivasi (p=0.007; OR=2.7), dukungan teman sebaya (p = 0.003; OR=2.9), dukungan tenaga kesehatan (p=0.000; OR=3.7), dan dukungan guru (p=0.014; OR=2.4) terhadap kepatuhan konsumsi Tablet Fe pada remaja putri. Analisis multivariat menunjukkan variabel yang paling dominan dalam kepatuhan konsumsi tablet Fe pada remaja putri adalah pengetahuan (p=0.000; OR=9.5).Simpulan: Terdapat faktor-faktor yang berhubungan signifikan dengan kepatuhan konsumsi tablet Fe seperti pengetahuan, sikap, motivasi, dukungan teman sebaya, dukungan petugas kesehatan, dan dukungan guru.Saran: Supaya meningkatkan promosi kesehatan secara terjadwal mengenai manfaat tablet Fe dan melakukan pemeriksaan HB minimal setahun sekali.